2017
DOI: 10.1091/mbc.e17-04-0252
|View full text |Cite
|
Sign up to set email alerts
|

Condensin II plays an essential role in reversible assembly of mitotic chromosomes in situ

Abstract: A modified protocol for inducing reversible assembly of mitotic chromosomes in situ is developed. As judged by this assay, which is combined with quantitative morphological analyses using a supervised machine-learning algorithm, condensin II plays a crucial role in both the recovery of chromatin shapes and the reorganization of chromosome axes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…The condensin I complex plays an important role in chromosome condensation and segregation. 12,13 The aberrant expression of the subunits of the complex causes incomplete chromosome condensation. 14 NCAPH is a part of the condensin complex.…”
Section: Discussionmentioning
confidence: 99%
“…The condensin I complex plays an important role in chromosome condensation and segregation. 12,13 The aberrant expression of the subunits of the complex causes incomplete chromosome condensation. 14 NCAPH is a part of the condensin complex.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of condensins has been show to result in “fuzzy” chromosomes in organisms from Drosophila to human (Somma et al, 2003, Hudson et al, 2003, Ono et al, 2003), with recent experiments showing that metaphase chromosome structure is particularly sensitive to depletion of condensin II (Ono et al, 2017). It has been established that condensin I and II are differentially distributed along mitotic chromatids (Ono et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These conclusions were mainly reached from imaging studies of fixed cells or using chromosome reconstitution in cell extracts. It is still unclear how condensins globally organize mitotic chromosome structure and quantitatively contribute to chromosome mechanical stiffness and stability, although a few studies have shown that metaphase chromosomes depleted in condensin have a more swollen conformation and are more easily deformed by hydrodynamic shear flow than unperturbed chromosomes (Green et al, 2012, Hudson et al, 2003, Ono et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…31 We have also measured morphological changes of the nucleolus and mitotic chromosomes upon depletion of the cellular components in cell lines. 32,33 Here using wndchrm, we quantitatively investigated morphological features and classification of gastric cancer tissues that included heterogeneous cell populations. Our results indicated that wndchrm reliably computes morphological changes of tumors with differentiation grades, and that cancer-associated protein-based analysis emphasized a correlation between molecular expression and tissue structures.…”
mentioning
confidence: 99%